The application of health literacy measurement tools (collective or individual domains) in assessing chronic disease management: a systematic review protocol. Issue 1 (December 2016) - Shum, Jessica; Poureslami, Iraj; Doyle-Waters, Mary; FitzGerald, J.
Abstract Background The term "health literacy" (HL) was first coined in 1974, and its most common definition is currently defined as a person's ability to access, understand, evaluate, communicate, and use health information to make decisions for one's health. The previous systematic reviews assessing the effect of existing HL measurement tools on health outcomes have simply searched for the term "health literacy" only to identify measures instead of incorporating either one or more of the five domains in their search. Furthermore, as the domain "use" is fairly new, few studies have actually assessed this domain. In this protocol, we propose to identify and assess HL measures that applied the mentioned five domains either collectively or individually in assessing chronic disease management, in particular for asthma and chronic obstructive pulmonary disease (COPD). The ultimate goal is to provide recommendations towards the development and validation of a patient-centric HL measurement tool for the two diseases. Methods/design A comprehensive, electronic search will be conducted to identify potential studies dating from 1974 to 2016 from databases such as Embase, MEDLINE, CINAHL, Cochrane Central Register of Controlled Trials, Web of Science, ERIC, PsycINFO, and HAPI. Database searches will be complemented with grey literature. Two independent reviewers will perform tool selection, study selection, data extraction, and quality assessment using pre-designed study forms. Any disagreement will be resolved through discussion or a third reviewer. Only studies that have developed or validated HL measurement tools (including one or more of the five domains mentioned above) among asthma and COPD patients will be included. Information collected from the studies will include instrument details such as versions, purpose, underlying constructs, administration, mapping of items onto the five domains, internal structure, scoring, response processes, standard error of measurement (SEM), correlation with other variables, clinically important difference, and item response theory (IRT)-based analyses. The identified strengths and weaknesses as well as reliability, validity, responsiveness, and interpretability of the tools from the validation studies will also be assessed using the COSMIN checklist. A synthesis will be presented for all tools in relation to asthma and COPD management. Discussion This systematic review will be one of several key contributions central to a global evidence-based strategy funded by the Canadian Institutes of Health Research (CIHR) for measuring HL in patients with asthma and COPD, highlighting the gaps and inconsistencies of domains between existing tools. The knowledge generated from this review will provide the team information on (1) the five-domain model and cross domains, (2) underlying constructs, (3) tool length, (4) time for completion, (5) reading level, and (6) format for development of the proposed tool. Other aspects of the published validation studies such as reliability coefficients, SEM, correlations with other variables, clinically important difference, and IRT-based analyses will be important for comparison purposes when testing, interpreting, and validating the developed tool. Systematic review registration PROSPEROCRD42016037532